THE INFLUENCE OF THE NUMBER OF POPULATION, THE NUMBER OF POOR POPULATION, NUMBER OF LABOR FORCES AND GROWTH RATE OF GRDP PERCAPITA OF ACEH PROVINCE - Mauliza; Murtala; Hendra Raza (Universitas Efarina, 2022)
The study examined the effect of population, the number off poor people, and the number of labor forces on the growth rate of GRDP percapita of Aceh Province. This study used time-series data obtained from the central Bureau of Statistic for Aceh province in 2007-2020. The data analysis method used was multiple linear regression analysis using the ECM (Error Correction Model) model approach with the help of Eviews 10. The results of the partial study showed that the population had a positive and significant effect on the growth rate of GRDP percapita of Aceh Province, the number of poor people had no positive and insignnificant effect on the growth rate of GRDP percapita, and the number of labor forces had no positive and insignificant effect of GRDP percapita of Aceh Province. Simultaneously, the population, the number of poor people and the number of labor forces had a positive and significant effect on the growth rate of GRDP percapita of Aceh Province.